Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/modpathol.2014.141
|View full text |Cite
|
Sign up to set email alerts
|

Continued observation of the natural history of low-grade ductal carcinoma in situ reaffirms proclivity for local recurrence even after more than 30 years of follow-up

Abstract: Opportunities to study the natural history of ductal carcinoma in situ are rare. A few studies of incompletely excised lesions in the premammographic era, retrospectively recognized as ductal carcinoma in situ, have demonstrated a proclivity for local recurrence in the original site. The authors report a follow-up study of 45 women with low grade ductal carcinoma in situ treated by biopsy only, recognized retrospectively during a larger review of surgical pathology diagnoses and original histologic slides for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 33 publications
0
81
0
Order By: Relevance
“…This indicates a substantial tendency for low-grade DCIS to recur locally when there is inadequate excision. In addition, as mentioned above, although the natural history of DCIS is not well understood due to surgical intervention, studies [13][14][15][16][17] investigating the outcome of women diagnosed with DCIS treated only with biopsy have shown that low-grade DCIS, when left untreated, has a propensity for local invasive recurrence even after long follow-up periods of more than 40 years, and that it is important not to overlook them. Details of the ipsilateral recurrences in our study cohort in Table 5 showed a number of intermediateand high-grade DCIS and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a substantial tendency for low-grade DCIS to recur locally when there is inadequate excision. In addition, as mentioned above, although the natural history of DCIS is not well understood due to surgical intervention, studies [13][14][15][16][17] investigating the outcome of women diagnosed with DCIS treated only with biopsy have shown that low-grade DCIS, when left untreated, has a propensity for local invasive recurrence even after long follow-up periods of more than 40 years, and that it is important not to overlook them. Details of the ipsilateral recurrences in our study cohort in Table 5 showed a number of intermediateand high-grade DCIS and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Natural history studies suggest that some patients do not develop invasive breast cancer without treatment, even after long follow-up [1][2][3][4][5]. Although current clinicopathologic features and risk models stratify DCIS patients into different risk groups, the currently available clinical tools are imperfect [6][7][8], and in an individual case, it is difficult to predict the risk of invasive disease.…”
Section: Introductionmentioning
confidence: 97%
“…30 Sixteen of these low-grade DCIS patients developed invasive carcinoma in the same breast quadrant within three to 42 years after initial biopsy. 30 More recently, Maxwell et al reported a series of 89 DCIS patients who either declined or were unfit to undergo surgery. 31 One in three patients developed invasive carcinoma after a median interval of 45 months, and high-grade DCIS patients showed a significantly higher risk for developing invasive carcinoma (48%) than intermediate or lowgrade DCIS patients (32 and 18%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…reported on a cohort of 45 patients with low‐grade DCIS, initially diagnosed as having benign breast disease and therefore “treated” with biopsy only . Sixteen of these low‐grade DCIS patients developed invasive carcinoma in the same breast quadrant within three to 42 years after initial biopsy . More recently, Maxwell et al .…”
Section: Introductionmentioning
confidence: 99%